Desenvolvimento de um equipamento para avaliação da susceptibilidade à fragilização por hidrogênio - Martiniano, Guilherme Antonelli (2016)
Hydrogen embrittlement of metallic materials has been a frequent problem in different industry sectors. Because it is the smallest existing atom, hydrogen diffuses into the microstructure of metallic materials, resulting in internal mechanical stresses that may eventually lead to a catastrophic failure. The most common methods available to analyze this phenomenon are time consuming and expensive. For this reason, it is desired to develop a test method that does not have such disadvantages. In this work it is presented the development of an equipment to rapidly evaluate the susceptibility to hydrogen embrittlement (SHE) of the metallic materials using the rising step load (RSL) bend testing in assisted environment. This equipment has a great advantage over the other evaluation methods of SHE, which is the shortest test time to have representative results. The validation of the infrastructure was performed by testing bars without notches to, whose measured mechanical stress was compared with that returned by the RSL software. In addition, the measurement uncertainty related to the calculation of the mechanical stress in the sample was calculated. The tests to verify the performance of the RSL equipment were carried out on samples of steel AISI 4140 heat treated to a hardness of 40HRC. The effect of the cathodic potential applied to notched bars of AISI 4140 on the SHE was evaluated. The results obtained in the validation phase of the equipment showed errors lower than 1%. The results showed also an increase in SHE with increasing material hardness indicating that there is a high sensitivity to the SHE with respect to the hardness of the sample. The tests carried out using cathodic potential variation showed a direct relationship between this parameter and the SHE of the sample, with saturation of the SHE at -1.1 VAg/AgCl.